Collection development and standards for protected area libraries a collection assessment of NIPA-CPPAP Library - Lim, Judy Joanne R.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
NIPA Incorporated is a consortium of leading Philippine civil society organizations involved in environmental and developmental work and it has evolved as a premier organization on protected area management in the Philippines. It is a recipient of 20 million dollar grant from the Global Environmental Facility (GEP) and works with the Department of Environment and Natural Resources (DENR) and the World Bank in the implementation of the Conservation of Priority protected Areas Project (CPPAP) that pilot tests that NIPAS' Law. The CPPAP has a time frame of 7 years (1994-2001) and ten sites are selected based on their biogeographic location biodiversity importance, funding needs and legal status as a conservation area.
The NIPA-CPPAP Library holds approximately 500 volumes of books, site reports, pamphlets, and brochures, journals of which 57 are Filipiniana titles and 35 are foreign titles, and accomplishment reports from the ten sites that are annually passed to the World Bank. It was only in 1999 that the Project coordinating Unit (PCU) turned over the said library holdings which made the library formally established only in the year 2000.NIPA Incorporated proposes a Protected Area Training Institute with the primary aim of developing a critical mass of personnel involved in PA management through the development of training curriculum and training materials, establishment of a resource center, and networking with the institutions supportive of PA management in the next three years.
This study tried to evaluate NIPA Library's collection and to find out the extent of compliance with existing policies and standards for collection development on protected area libraries. The researcher tried to find counterparts of the PA Institute abroad to check what library materials they maintained in their libraries and if they follow existing policies and standards, which would be used as a guide in evaluating NIPA Library's current collection.
Since no specific collection development policies on PA libraries exist, the researcher instead resorted to gathering general collection development policies and collected clippings on related topics like Marine Protected Areas Libraries and some protected area resource centers to check on the library collections they maintain.
The exhaustiveness of NIPA Library's collection was assessed using the techniques utilized by York University Libraries. Six Protected Area Management Categories were used as defined by IUCN (International Union for Conservation of Nature and Natural Resources) for the purpose of assessing the collecting level of NIPA Library's collection. As part of the evaluation, the overall collection of the library was determined and categorized. Titles/volumes for each library material were tallied and totaled.
The setting up of the proposed PA Training Institute would still be a long way ahead and it would still require much preparation. If the PA Institute will use NIPA Library as its major resource center, the NIPA Library should acquire more relevant and up to date reference materials. They should also consider tapping library resources from library networks and consortiums to support the PA Institute curricular offerings.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: NIPA-CPPAP Library -- Evaluation